Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan Sektor Consumer Goods dan Mining di Bursa Efek Indonesia (BEI) Periode 2018–2020 - Fenina Niken Pratiwi; Aljufri Aljufri; Arini Arini (Politeknik Negeri Bengkalis, 2022)
In general, companies have three main goals that are mutually sustainable: maximizing profits, prospering shareholders, and maximizing company values. This research intends to determine the value of consumer goods and mining sector companies in Indonesia Stock Exchange (IDX) during 2018-2020 based on: (1) investment decisions, (2)financing decisions, and (3)dividend policies. The sampling technique used is purposive sampling, and obtained 25 companies that met the criteria as research samples. The statistical method used is multiple linear regression analysis with SPSS version 25. The results show that funding decisions have a significant effect on firm value, while investment decisions and dividend policies have no significant effect on firm value.Keywords: dividend policy, firm value, funding decision, investment decision